Archival processing of the Burgos family photograph collection - Deloria, Michelle R. (School of Library and Information Studies, University of the Philippines, Diliman, 2019)
The initial conception of the project in 2018 was assessed based on the socio-political and historical value of the Burgos family photograph collection. The Burgos family photograph collection included is the published and unpublished (black and white, and colored) photographs, from 1984 to 1995 (including undated photographs). Most of these photographs were published in their newspapers such as the Bicol Forum, People‘s Voice, Sunday, Ang Bagong Masa, Ang Pahayagang Malaya, Metropolitan Mail, Midday, Ang Tinig ng Masa, and the WE Forum. Some photographs were also published in other newspapers which the Burgos Family did not own such as, Ang Bayan Ko, Bicolandia, Ito ang Pilipinas, Monitor, Pare Ko, People‘s Tonite, Talarawan, and Taliba. The photographers originally owned the photographs that were used in other publications but were submitted to the WE Forum and Malaya. This project recognizes that the photographers were the original owners of the photographs as they submitted these to the WE Forum and Malaya. However, some were not labelled, hence even the Burgos Family could not ascertain the provenance of the photos.